MOLECULAR SCREENING OF POTATO VARIETIES BRED IN THE NORTHWESTERN ZONE OF THE RUSSIAN FEDERАTION - Т. A. Gavrilenko; N. S. Klimenko; O. Yu. Antonova; V. A. Lebedeva; Z. Z. Evdokimova; N. M. Gadjiyev; O. V. Apalikova; N. V. Alpatyeva; L. I. Kostina; N. M. Zoteyeva; F. T. Mamadbokirova; K. V. Egorova (Вавиловский журнал генетики и селекции)
Increasing the resistance of varieties to diseases and pests is a priority in potato breeding. Many potato varieties created in the Leningrad Scientific Research Institute of Agriculture “Belogorka” are multi-species hybrids possessing complex resistance to the most spread pathogens in combination with a high plasticity, which determined their zoning in many regions of the Russian Federation. Potato varieties and hybrids created in different periods of time in this institute and in the Ltd Breeding company “LiGa” were included in marker-assisted selection with 22 markers of 14 R genes conferring extreme resistance to viruses PVY and PVX, resistance to cyst nematodes Globodera pallida (patotypes Pa2, Pa3) and G. rostochiensis (pathotype Ro1) and resistance to late blight. The data of molecular screening were compared with the results of the State Test of Varieties for Disease Resistance, as well as with other published sources. Markers of sterile and fertile cytoplasm types were also used in the study. Based on the results of molecular screening, varieties and hybrids with different combinations of markers of R genes conferring resistance to the most harmful pathogens (Rysto, Ry-fsto, Rx1, Rx2, Gro1-4, H1, Gpa2, R1, R3a, Rpi-blb1, Rpi-sto1) were detected. Among them, genotypes with sterile D-, T-, W/gamma cytoplasmic types were selected. Analysis of their pollen fertility, crossability and pedigree data showed that breeders succeed in obtaining fertile forms with the D- and T-types of cytoplasm carrying genetic material of Mexican polyploid species Solanum stoloniferum and S. demissum. The information about the presence of markers of R genes and about cytoplasm types of hybrids and varieties will allow an effective implementation of further breeding programs for resistance to a complex of pathogens, including pyramiding of R genes. The data of molecular screening made it possible to specify the pedigrees of several varieties and hybrids that have been created over several decades.